Mathematical modeling of recombinant Escherichia coli aerobic batch fermentations - Costa, Rafael S. (2008)
In this work, three competing unstructured mathematical models for the biomass growth by recombinant E. coli strains with different acetate inhibition kinetics terms were evaluated for batch processes at constant temperature and pH. The models considered the dynamics of biomass growth, acetate accumulation, substrate consumption, Green Fluorescence Protein (GFP) production and three metabolic pathways for E. coli. Parameter estimation and model validation was carried out using the Systems Biology toolbox for Matlab (The Mathworks) with different initial glucose concentrations (5g/kg to 25g/kg) in a 5dm3 bioreactor. Model discrimination was based on the two model selection criterion (Akaike’s information criterion and normalized quadratic difference between the simulated and experimental data criterion). The first model described by Jerusalimsky approach is an approximation to the non-competitive substrate inhibition. Cockshott approach describes the inhibition at high acetate levels and Levenspiel considers the critical inhibitory acetate concentration that limits growth. Within the studied experimental range, Jerusalimsky model provided a good approximation between real and simulated values and should be favored. The model describes the experimental data satisfactorily well.